Practices around Working from Home and Early Indicators on Returning to Work after the COVID-19 Pandemic: Data from Microsoft China - Wang, Yun; Liu, Ying; Cui, Weiwei; Tang, John; Zhang, Haidong; Walston, Doug; Zhang, Dongmei (2020)
An online survey administered to employees of Microsoft China during the COVID-19 pandemic gathered information about their practices around working from home and their return to work after the soft re-opening of their workplaces. The 475 responses from the Beijing, Shanghai, and Suzhou sites provide a comparison for how the practices in China are similar to or different from data reported in other parts of the world. Since workplaces in China opened earlier than many places in the world, the data also give early indicators around practices in returning to work. The data show how employees enacted a hybrid work practice mixing working from home and going into the office, and what factors led to their decisions about how to return to work. About the author/s Yun Wang Microsoft Research Asia wangyun@microsoft.com Ying Liu Microsoft STC Asia liyin@microsoft.com Weiwei Cui Microsoft Research Asia weiweicu@microsoft.com John Tang Microsoft Research Redmond johntang@microsoft.com Haidong Zhang Microsoft Research Asia haizhang@microsoft.com Doug Walston Microsoft STC Asia dowalsto@microsoft.com Dongmei Zhang Microsoft Research Asia dongmeiz@microsoft.com New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).